Detection of sub-ppm Concentrations of Ammonia in an Ionic Liquid: Enhanced Current Density Using "Filled" Recessed Microarrays - Hussain, G.; Silvester, Debbie (American Chemical Society, 2016)
The voltammetric detection of less than 1 ppm of ammonia gas in the room temperature ionic liquid (RTIL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C2mim][NTf2]) is demonstrated using low-cost planar electrode devices. Three commercially available planar devices were employed, all with platinum (Pt) working electrodes: a thin-film electrode (TFE), a screen-printed electrode (SPE), and a microarray thin film electrode (MATFE), along with an "ideal" conventional Pt microdisk electrode for comparison. The microholes on the recessed MATFE were also "filled" with electrodeposited platinum, to improve radial diffusion characteristics to the microhole and generate higher current densities. Current density was lowest for the TFE and SPE surfaces (linear diffusion), higher for the MATFE (mixed radial and linear diffusion), and even higher for the filled MATFE (predominantly radial diffusion). Linear sweep voltammetry (LSV) and potential-step chronoamperometry (PSCA) at 10-100 ppm of NH3 gave linear behavior for current vs concentration. Limits of detection (LODs) were in the range of ca. 1-9 ppm, lower than the minimum exposure limit (25 ppm) for NH3. The best stability, reproducibility, and the lowest LODs were observed on the recessed and filled MATFEs. These were employed to detect lower concentrations of ammonia (0.1-2 ppm), where linear behavior was also observed, and LODs of 0.11 (recessed) and 0.02 (filled) were obtained. These are believed to be the lowest LODs (to date) reported for ammonia gas in neat ionic liquids. This is highly encouraging and suggests that RTILs and low-cost miniaturized MATFEs can be combined in amperometric sensor devices to easily and cheaply detect ammonia gas at ppb concentrations. (Graph Presented).